Potential for drug interactions involving cytochrome P450 in patients attending palliative day care centres: a multicentre audit. - Wilcock, A; Thomas, J; Frisby, J; Webster, M; Keeley, V; Finn, G; Fossey, K; Wee, B; Beale, J; Lennard, MS (2005)
AIM: To determine the potential for drug interactions involving cytochrome P450 (CYP) in patients receiving palliative day care. METHODS: Drugs used by patients attending four specialist palliative day care centres were reviewed to identify combinations that could result in a pharmacokinetic interaction via any of the five main human forms of CYP. RESULTS: Of 160 patients, 145 (91%) were prescribed at least one drug that was a substrate, inhibitor or inducer of one of the five main CYP isoforms. Twenty-four drug combinations, involving 34 patients, could have given rise to a clinically important interaction. CONCLUSIONS: Prescribers should be aware that in this group of patients, one in five are at risk of a clinically important CYP-mediated drug interaction.